Membrane electrode for hydrogen production through water electrolysis, preparation method of membrane electrode and water electrolysis equipment
By using gradient catalyst distribution and molybdenum-based modification layer in PEM electrolytic membrane electrode, the problems of high cost and unstable structure of noble metal catalysts are solved, the efficiency and safety of electrolytic hydrogen production are improved, and the membrane electrode is extended Service life.
Patent Information
- Application Number
- CN202410908504.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-08
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-07-08
AI Technical Summary
The existing PEM electrolytic hydrogen production technology is caused by high cost of precious metal catalysts, unstable catalyst layer structure and safety hazards. The catalyst utilization rate is low and it is easy to form scale to affect the reaction.
Design a membrane electrode, including a gradient anode and cathode catalytic layer on both sides of the proton exchange membrane, and a molybdenum-based modified layer between the anode catalytic layer and the proton exchange membrane, using MoS2/C or MoO2/C composite materials as catalysts , improve catalyst distribution and structural stability, and a detachable modified layer is provided on the outside of the cathode catalytic layer to adsorb scale ions.
It improves the catalytic efficiency and safety performance of hydrogen production in electrolytic water, extends the service life of the membrane electrode, reduces the concentration of hydrogen on the oxygen evolution side, enhances the mechanical strength of the membrane electrode, and improves the hydrogen yield and catalyst utilization rate.
Smart Images

Figure CN119162603A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of membrane electrode technology, and in particular to a membrane electrode for hydrogen production by water electrolysis, its preparation method and water electrolysis equipment. Background Technology
[0002] Due to rapid societal development and the increasing demand for energy, coupled with the global energy transition, hydrogen energy has garnered widespread attention as a clean energy source and energy carrier with high energy density and zero pollution. PEM (Proton Exchange Membrane) water electrolysis for hydrogen production has become a research hotspot, as it can effectively couple renewable energy sources to hydrogen production. The PEM water electrolysis membrane electrode mainly consists of a proton exchange membrane, an anode catalyst layer, and a cathode catalyst layer. However, PEM water electrolysis for hydrogen production is limited by key materials such as the proton exchange membrane and precious metal catalysts. Currently, platinum and other precious metals are still used as catalysts in the water electrolysis catalytic reaction, resulting in high production costs. Furthermore, catalyst particle agglomeration occurs during the catalyst layer fabrication process, and cracking and detachment of the catalyst layer occur with increasing usage time, leading to reduced catalyst utilization and low catalytic efficiency. Currently, the catalyst layer is often prepared by directly using the proton exchange membrane as the support layer, attaching the catalyst material to both sides of the proton exchange membrane to form a catalyst coating film. However, during the preparation process, the polar solvent in the catalyst coating film easily comes into contact with the proton exchange membrane, causing swelling and affecting the structural stability of the catalyst coating film, thus impacting electrolysis efficiency. During water electrolysis, due to the pressure difference between the hydrogen evolution side and the oxygen evolution side within the electrolyzer, hydrogen gas easily diffuses towards the oxygen evolution side. If the concentration of the mixed hydrogen and oxygen reaches a certain level, it can easily lead to an explosion hazard. With the use of hydrogen electrolyzers, scale easily forms on the cathode catalyst layer, affecting the hydrogen evolution reaction. Summary of the Invention
[0003] Therefore, embodiments of this application provide a membrane electrode for hydrogen production via water electrolysis, which improves hydrogen production efficiency and yield.
[0004] In one aspect, this application provides a membrane electrode for producing hydrogen by electrolysis of water.
[0005] This application is achieved through the following technical solution:
[0006] A membrane electrode for producing hydrogen by water electrolysis, the membrane electrode comprising:
[0007] A proton exchange membrane, comprising an anode catalytic layer, a cathode catalytic layer, and an anode modification layer disposed on both sides of the proton exchange membrane;
[0008] The content of the anodic catalyst in the anodic catalyst layer increases from the side closer to the proton exchange membrane to the side farther away from the proton exchange membrane;
[0009] The content of the cathode catalyst in the cathode catalyst layer increases from the side closer to the proton exchange membrane to the side farther away from the proton exchange membrane.
[0010] An anode modification layer is disposed between the anode catalyst layer and the proton exchange membrane, and the anode modification layer contains a molybdenum-based catalyst for catalyzing the oxidation reaction of hydrogen.
[0011] In a preferred embodiment of this application, the molybdenum-based catalyst in the anode modification layer may be further configured to include at least one of MoS2 / C composite material and MoO2 / C composite material.
[0012] In a preferred embodiment of this application, the membrane electrode may further include a cathode modification layer; the cathode modification layer is disposed outside the cathode catalyst layer and is used to adsorb scale-forming ions in the electrolyzed water.
[0013] In a preferred embodiment of this application, the cathode catalyst layer may be further configured such that the cathode catalyst layer comprises a first cathode catalyst layer located near the proton exchange membrane and a second cathode catalyst layer located away from the proton exchange membrane; the loading of cathode catalyst in the first cathode catalyst layer is greater than the loading of cathode catalyst in the second cathode catalyst layer.
[0014] In a preferred embodiment of this application, the loading of the cathode catalyst in the first cathode catalyst layer can be further configured as 1.5 mg / cm³. 2 ~2.0mg / cm 2 The loading of the cathode catalyst in the second cathode catalyst layer is 1.0 mg / cm³. 2 ~1.5mg / cm 2 .
[0015] In a preferred embodiment of this application, the first cathode catalytic layer and the second cathode catalytic layer are both prepared from cathode catalytic slurry.
[0016] The cathode catalytic slurry comprises a cathode catalyst, an ionomer, a solvent, deionized water, and a dispersant; the cathode catalyst is a Pt / CNT composite material.
[0017] In a preferred embodiment of this application, the content of Pt can be further set to 25% to 35% based on the mass of the Pt / CNT composite material, and the average particle size of Pt can be 5 nm to 20 nm.
[0018] In a preferred embodiment of this application, the total thickness of the cathode catalyst layer may be further configured to be 5.0 μm to 10.0 μm.
[0019] In a preferred embodiment of this application, the anode catalyst layer may be further configured such that a first anode catalyst layer located near the proton exchange membrane and a second anode catalyst layer located away from the proton exchange membrane; the loading of the anode catalyst in the first anode catalyst layer is higher than the loading of the anode catalyst in the second anode catalyst layer.
[0020] In a preferred embodiment of this application, the loading of the anolyte catalyst in the first anolyte catalyst layer can be further configured as 2.5–3.5 mg / cm³. 2 The loading of the second anode catalyst is 2.0–2.5 mg / cm³. 2 .
[0021] In a preferred embodiment of this application, the first and second anode catalyst layers are both prepared from an anode catalyst slurry; the anode catalyst slurry includes an anode catalyst, an ionomer, a solvent, deionized water, and a dispersant; the anode catalyst includes one or more of Ir, IrO2, Ru, RuO2, and IrRuOx.
[0022] In a preferred embodiment of this application, the total thickness of the anode catalyst layer may be further configured to be 10 μm to 20 μm.
[0023] In a preferred embodiment of this application, the proton exchange membrane may be further configured to be selected from at least one of perfluorosulfonic acid proton exchange membranes, organic / inorganic nanocomposite proton exchange membranes, and fluorine-free proton exchange membranes.
[0024] Secondly, this application provides a method for preparing a membrane electrode for hydrogen production by water electrolysis.
[0025] This application is achieved through the following technical solution:
[0026] A method for preparing a membrane electrode for hydrogen production by water electrolysis, the method comprising:
[0027] Preparation of anode catalyst slurry: The anode catalyst is mixed with ionomer, solvent, deionized water and dispersant, and ultrasonically dispersed to obtain a uniform first anode catalyst slurry and second anode catalyst slurry;
[0028] Preparation of cathode catalytic slurry: The cathode catalyst is mixed with ion polymer, solvent, deionized water and dispersant, and then placed in a planetary ball mill for stirring and dispersion to obtain the first cathode catalytic slurry and the second cathode catalytic slurry;
[0029] Preparation of anode modified layer slurry: Molybdenum-based catalyst, porous carbon material, binder and viscosity modifier are mixed to form anode modified layer slurry;
[0030] An anode-modified layer slurry is coated onto one surface of a proton exchange membrane and dried to obtain an anode-modified layer attached to the proton exchange membrane.
[0031] The first anode catalyst slurry is coated onto the surface of the anode modified layer by a transfer method and then heated on a vacuum adsorption heating plate to form the first anode catalyst layer; the second anode catalyst slurry is coated onto the surface of the first anode catalyst layer by a transfer method and then heated on a vacuum adsorption heating plate to form the second anode catalyst layer.
[0032] The first cathode catalyst slurry is coated onto the other surface of the proton exchange membrane by a transfer method and then heated on a vacuum adsorption heating plate to form the first cathode catalyst layer; the second cathode catalyst slurry is coated onto the other surface of the proton exchange membrane by a transfer method and then heated on a vacuum adsorption heating plate to form the second cathode catalyst layer.
[0033] In a preferred embodiment of this application, a removable cathode modification layer may be mounted on the surface of the second cathode catalyst layer.
[0034] In a preferred embodiment of this application, the step of preparing the anode catalyst slurry may be further configured to include: mixing the anode catalyst, ionomer, solvent, deionized water and dispersant in a mass ratio of (20%–30%):(3%–8%):(30%–50%):(20%–45%):(1%–2%), and then ultrasonically dispersing the mixture to obtain a uniform first anode catalyst slurry.
[0035] In a preferred embodiment of this application, the step of preparing the anode catalyst slurry may be further configured to include: the step of preparing the anode catalyst slurry includes:
[0036] The anode catalyst, ionomer, solvent, deionized water and dispersant are mixed in the following mass ratios: (15%–20%): (3%–8%): (30%–45%): (25%–45%): (1%–2%) and ultrasonically dispersed to obtain a uniform second anode catalyst slurry.
[0037] In a preferred embodiment of this application, the step of preparing the cathode catalytic slurry may be further configured as follows: the cathode catalyst, ionomer, solvent, deionized water and dispersant are mixed in a mass ratio of (15% to 20%):(3% to 8%):(30% to 50%):(25% to 45%):(1% to 2%), and then stirred and dispersed in a planetary ball mill to obtain the first cathode catalytic slurry.
[0038] In a preferred embodiment of this application, the cathode catalyst, ionomer, solvent, deionized water and dispersant are mixed in a mass ratio of (10%–15%):(3%–8%):(30%–50%):(25%–45%):(1%–2%) and then stirred and dispersed in a planetary ball mill to obtain a second cathode catalyst slurry.
[0039] In a preferred embodiment of this application, the thickness of the anodic modification layer can be further set to 0.5 μm to 1.0 μm.
[0040] Thirdly, this application provides a water electrolysis device.
[0041] This application achieves its goal through the following technical solution:
[0042] An electrolysis water apparatus includes an electrolyzer comprising a membrane electrode assembly for producing hydrogen by electrolysis of water as described in the first aspect.
[0043] In summary, compared with the prior art, the beneficial effects of the technical solution provided in this application include at least the following:
[0044] The membrane electrode proposed in this application includes a proton exchange membrane, an anode catalyst layer and a cathode catalyst layer disposed on both sides of the proton exchange membrane, and an anode modification layer. The content of the anode catalyst in the anode catalyst layer increases from the side closer to the proton exchange membrane to the side farther away from the proton exchange membrane; the content of the cathode catalyst in the cathode catalyst layer increases from the side closer to the proton exchange membrane to the side farther away from the proton exchange membrane; and the anode modification layer is disposed between the anode catalyst layer and the proton exchange membrane, containing a molybdenum-based catalyst for catalyzing the oxidation reaction of hydrogen. By increasing the catalyst content in the direction farther away from the proton exchange membrane, the catalytic capacity within the catalyst layer is enhanced, thereby improving the catalytic performance of water electrolysis. Simultaneously, adding a molybdenum-based catalyst containing a catalyst capable of catalyzing the oxidation reaction of hydrogen on the anode catalyst side can reduce hydrogen on the oxygen evolution side, improve the safety performance during the water electrolysis hydrogen production catalytic process, and enhance catalytic efficiency. Attached Figure Description
[0045] Figure 1 A schematic diagram of the structure of a membrane electrode for hydrogen production by water electrolysis provided in an embodiment of this application;
[0046] Figure 2 A schematic diagram of the structure of a membrane electrode for hydrogen production by water electrolysis provided in another embodiment of this application;
[0047] Explanation of reference numerals in the attached figures:
[0048] Proton exchange membrane-1, cathode catalyst layer-2, first cathode catalyst layer-21, second cathode catalyst layer-22, anode modification layer-3, anode catalyst layer-4, first anode catalyst layer-41, second anode catalyst layer-42. Detailed Implementation
[0049] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
[0050] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0051] Furthermore, the term "and / or" in this application is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, the character " / " in this application, unless otherwise specified, generally indicates that the preceding and following related objects have an "or" relationship.
[0052] In this application, the terms "first," "second," etc., are used to distinguish identical or similar items with essentially the same function. It should be understood that there is no logical or temporal dependency between "first," "second," and "nth," nor are there any restrictions on quantity or execution order.
[0053] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.
[0054] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has "a" parts by mass and component B has "b" parts by mass, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it can mean that the mass of component A is aK and the mass of component B is bK (K is any number representing a multiplier). It is important to understand that, unlike the number of parts by mass, the sum of the mass parts of all components is not limited to 100 parts.
[0055] The embodiments of this application will now be described in further detail with reference to the accompanying drawings.
[0056] like Figure 1 As shown, the membrane electrode includes:
[0057] The proton exchange membrane 1 comprises a cathode catalytic layer 2, an anode modification layer 3, and an anode catalytic layer 4. The anode catalytic layer 4 and the cathode catalytic layer 2 are disposed opposite each other on both sides of the proton exchange membrane 1. The anode catalytic layer 4 is used to catalyze the production of oxygen, and the cathode catalytic layer 2 is used to catalyze the production of hydrogen. The proton exchange membrane 1 is selected from one of the following: perfluorosulfonic acid proton exchange membrane, organic / inorganic nanocomposite proton exchange membrane, and fluorine-free proton exchange membrane. The thickness of the proton exchange membrane is 30 μm to 60 μm.
[0058] An anode modification layer 3 is disposed between the anode catalytic layer 4 and the proton exchange membrane 1. This anode modification layer 3 contains a molybdenum-based catalyst for catalyzing the oxidation reaction of hydrogen. During water electrolysis, the pressure on the cathode hydrogen evolution side of the electrolyzer is greater than the pressure on the anode oxygen evolution side. As the pressure difference increases, hydrogen diffuses through the proton exchange membrane to the anode oxygen evolution side. The anode modification layer in this application catalyzes the hydrogen permeating from the cathode hydrogen evolution side to react before it reaches the anode oxygen evolution side, effectively reducing the hydrogen concentration on the anode oxygen evolution side, reducing safety hazards caused by hydrogen and oxygen contact, and improving the safety of the water electrolysis process. Simultaneously, the anode modification layer also enhances the mechanical strength of the proton exchange membrane, increases its service life, improves electrolysis performance, and thus increases hydrogen production.
[0059] The content of the anolyte catalyst in the anode catalyst layer 4 increases from the side closest to the proton exchange membrane 1 towards the side farther away from the proton exchange membrane; similarly, the content of the cathode catalyst in the cathode catalyst layer 2 increases from the side closest to the proton exchange membrane towards the side farther away from the proton exchange membrane. This application, through a gradient catalyst content design, increases the anolyte catalyst content and the cathode catalyst content in the anode catalyst layer 4 and the cathode catalyst layer 2 away from the proton exchange membrane 1, thereby providing more catalytic activation sites for the oxygen evolution reaction and the hydrogen evolution reaction, and improving the catalytic effect within the catalyst layers.
[0060] In some embodiments, such as Figure 2 As shown, the cathode catalyst layer 2 includes a first cathode catalyst layer 21 located near the proton exchange membrane 1 and a second cathode catalyst layer 22 located away from the proton exchange membrane 1; the loading of cathode catalyst in the first cathode catalyst layer 21 is greater than the loading of cathode catalyst in the second cathode catalyst layer 22. The loading of cathode catalyst in the first cathode catalyst layer 21 is 1.5 mg / cm³. 2 ~2.0mg / cm 2 The loading of the cathode catalyst in the second cathode catalyst layer 22 is 1.0 mg / cm³. 2 ~1.5mg / cm 2The total thickness of the cathode catalyst layer 2 is 5.0 μm to 10.0 μm, and can be 2.0 μm, 2.5 μm, 3.0 μm, 4.0 μm, 4.5 μm, or 5.0 μm, but is not limited to these values. Controlling the thickness of the cathode catalyst layer within the above range ensures good catalytic effect and good ion conduction rate. If the cathode catalyst layer is too thin, it will reduce the catalyst content, affecting the hydrogen evolution reaction on the cathode side and the efficiency of water electrolysis. If the cathode catalyst layer is too thick, it will affect the transport rate of hydroxide ions to the anode side, which will also affect the efficiency of water electrolysis.
[0061] Specifically, both the first and second cathode catalyst layers are prepared from cathode catalyst slurry; the cathode catalyst slurry comprises a cathode catalyst, an ionomer, a solvent, deionized water, and a dispersant. The cathode catalyst is a Pt / CNT composite material; the ionomer includes Nafion solution; the solvent includes at least one of isopropanol, n-propanol, tert-butanol, ethylene glycol, and glycerol; and the dispersant is at least one of polyacrylamide, sodium dimethyl sulfonate, and N-methylpyrrolidone.
[0062] Based on the mass of the Pt / CNT composite material, the Pt content is 25%–35%; the average Pt particle size is 5 nm–20 nm. Pt nanoparticles are supported on highly conductive carbon nanotubes and highly uniformly dispersed on the cathode catalyst layer, effectively improving the electrochemical catalytic activity and utilization rate of the catalyst. CNTs have an excellent specific surface area, which can reduce Pt aggregation, expose more active sites, and improve the electrochemical activity of the catalyst.
[0063] The anode catalyst layer 4 includes a first anode catalyst layer 41 located near the proton exchange membrane 1 and a second anode catalyst layer 42 located away from the proton exchange membrane 1; the loading of the anode catalyst in the first anode catalyst layer 41 is higher than that in the second anode catalyst layer 42. The loading of the anode catalyst in the first anode catalyst layer 41 is 2.5–3.5 mg / cm³. 2 The loading of the second anode catalyst 42 is 2.0–2.5 mg / cm³. 2 The total thickness of the anode catalyst layer is 10μm to 20μm, and can be 10μm, 12μm, 14μm, 16μm, 18μm, or 20μm, but is not limited to these values.
[0064] The first anode catalyst layer 41 and the second anode catalyst layer 42 are both prepared from anode catalyst slurry; the anode catalyst slurry includes anode catalyst, ion polymer, solvent, deionized water and dispersant.
[0065] The anode catalyst includes one or more of Ir, IrO2, Ru, RuO2, and IrRuOx; the ionomer is a Nafion solution; the solvent includes at least one of isopropanol, n-propanol, tert-butanol, ethylene glycol, and glycerol; and the dispersant is at least one of polyacrylamide, sodium dimethyl sulfonate, and N-methylpyrrolidone. Adding a dispersant during the preparation of the cathode and anode catalyst slurries can effectively reduce catalyst particle agglomeration loss and deactivation, and improve the durability of the catalyst particles.
[0066] In some embodiments, the molybdenum-based catalyst in the anode modification layer includes at least one of MoS2 / C composite material and MoO2 / C composite material. A slurry is prepared by mixing the MoS2 / C composite material or MoO2 / C composite material with porous carbon material and a binder, and the slurry is coated onto the surface of the proton exchange membrane. The thickness of the anode modification layer is 0.5 μm to 1.0 μm, preferably 0.8 μm. The MoS2 / C composite material and / or MoO2 / C composite material in the anode modification layer can catalyze the hydrogen reaction. Simultaneously, the MoS2 / C composite material and / or MoO2 / C composite material exhibit good electrical conductivity and oxygen evolution reaction catalytic activity, enabling the elimination of hydrogen while promoting the oxygen evolution reaction. The porous carbon material and binder can form a three-dimensional network structure, which can act as a deformation suppression layer for the proton exchange membrane, effectively reducing the swelling and deformation of the proton exchange membrane, improving structural stability, and thus enhancing catalytic performance.
[0067] In some embodiments, the membrane electrode further includes a cathode modification layer, which is detachably disposed on the outside of the cathode catalyst layer for adsorbing scale-forming ions in the electrolyzed water. The cathode modification layer can be snap-fitted onto the outside of the cathode catalyst layer during the assembly of the water electrolysis equipment. Before the water electrolysis reaction, a potential lower than that of the cathode catalyst layer is applied to the cathode modification layer, causing it to adsorb most of the scale-forming ions such as calcium and magnesium from the cathode-side water, preventing scale formation on the cathode catalyst layer and improving the stability and service life of the catalyst layer. The cathode modification layer is made of stainless steel.
[0068] The method for preparing the membrane electrode includes:
[0069] Preparation of anode catalyst slurry: The anode catalyst is mixed with ionomer, solvent, deionized water and dispersant, and ultrasonically dispersed to obtain a uniform first anode catalyst slurry and a second anode catalyst slurry; wherein, the mass ratio of anode catalyst to ionomer, solvent, deionized water and dispersant in the first anode catalyst slurry is (20%~30%):(3%~8%):(30%~50%):(20%~45%):(1%~2%); the mass ratio of anode catalyst to ionomer, solvent, deionized water and dispersant in the second anode catalyst slurry is (15%~20%):(3%~8%):(30%~45%):(25%~45%):(1%~2%).
[0070] Preparation of cathode catalytic slurry: The cathode catalyst is mixed with ionomer, solvent, deionized water and dispersant in a mass ratio and placed in a planetary ball mill for stirring and dispersion to obtain a first cathode catalytic slurry and a second cathode catalytic slurry; wherein, the mass ratio of cathode catalyst to ionomer, solvent, deionized water and dispersant in the first cathode catalytic slurry is (15%~20%):(3%~8%):(30%~50%):(25%~45%):(1%~2%); the mass ratio of cathode catalyst to ionomer, solvent, deionized water and dispersant in the second cathode catalytic slurry is (10%~15%):(3%~8%):(30%~50%):(25%~45%):(1%~2%).
[0071] Preparation of anode modified layer slurry: Molybdenum-based catalyst, porous carbon material, and binder are mixed to form anode modified layer slurry;
[0072] An anode-modified layer slurry is coated on one surface of a proton exchange membrane and dried to obtain an anode-modified layer attached to the proton exchange membrane; the thickness of the anode-modified layer is 0.5 μm to 1.0 μm.
[0073] The first anode catalyst slurry is coated onto the surface of the anode modified layer by a transfer method and then heated on a vacuum adsorption heating plate to form the first anode catalyst layer; the second anode catalyst slurry is coated onto the surface of the first anode catalyst layer by a transfer method and then heated on a vacuum adsorption heating plate to form the second anode catalyst layer.
[0074] The first cathode catalyst slurry is coated onto the other surface of the proton exchange membrane by a transfer method and then heated on a vacuum adsorption heating plate to form the first cathode catalyst layer; the second cathode catalyst slurry is coated onto the other surface of the proton exchange membrane by a transfer method and then heated on a vacuum adsorption heating plate to form the second cathode catalyst layer.
[0075] Assemble a water electrolysis device, which includes an electrolyzer comprising the aforementioned membrane electrode assembly (MEA) for hydrogen production via water electrolysis. A cathode diffusion layer is also included outside the cathode catalyst layer of the MEA, and an anode diffusion layer is included outside the anode catalyst layer. The anode and cathode diffusion layers are selected from nickel foam, nickel fiber felt, nickel braided mesh, and nickel expanded mesh.
[0076] Example 1
[0077] Preparation of anode catalyst slurry: IrO2, Nafion solution, isopropanol, deionized water, and N-methylpyrrolidone were mixed in a mass ratio of 20%:8%:25%:45%:2% and ultrasonically dispersed for 2.0 h to obtain a uniform first anode catalyst slurry; IrO2, Nafion solution, isopropanol, deionized water, and N-methylpyrrolidone were mixed in a mass ratio of 15%:8%:30%:45%:2% and ultrasonically dispersed for 2.0 h to obtain a uniform second anode catalyst slurry;
[0078] Preparation of cathode catalytic slurry: The cathode catalyst was mixed with ionomer, solvent, deionized water and dispersant in a mass ratio of 15%:8%:30%:45%:2%, and stirred in a planetary ball mill at 2500 rpm for 1.0 h; The cathode catalyst was mixed with ionomer, solvent, deionized water and dispersant in a mass ratio of 10%:8%:35%:45%:2%, and stirred in a planetary ball mill at 2500 rpm for 1.0 h to obtain the second cathode catalytic slurry.
[0079] Preparation of anode modified layer slurry: MoS2 / C composite material, carbon nanotubes and epoxy resin are mixed in a mass ratio of 10%:60%:30% to form anode modified layer slurry;
[0080] An anode-modified layer slurry was coated onto one surface of a perfluorosulfonic acid proton exchange membrane and dried to obtain an anode-modified layer attached to the perfluorosulfonic acid proton exchange membrane; the thickness of the anode-modified layer was 0.5 μm.
[0081] The first anode catalyst slurry was coated onto the surface of the anode modified layer by a transfer method, and then heated on a vacuum adsorption heating plate at 80°C for 2.0 h to form the first anode catalyst layer; the second anode catalyst slurry was coated onto the surface of the first anode catalyst layer by a transfer method, and then heated on a vacuum adsorption heating plate at 80°C for 2.0 h to form the second anode catalyst layer. The total thickness of the anode catalyst layer was 10 μm.
[0082] The first cathode catalyst slurry was coated onto another surface of the membrane using a transfer method, and then heated on a vacuum adsorption heating plate at 75°C for 2.0 hours to form the first cathode catalyst layer. The second cathode catalyst slurry was coated onto another surface of the perfluorosulfonic acid proton exchange membrane using a transfer method, and then heated on a vacuum adsorption heating plate at 75°C for 2.0 hours to form the second cathode catalyst layer. The total thickness of the cathode catalyst layer was 5 μm.
[0083] Example 2
[0084] Preparation of anode catalyst slurry: IrO2, Nafion solution, isopropanol, deionized water, and N-methylpyrrolidone were mixed in a mass ratio of 30%:5%:35%:28%:2% and ultrasonically dispersed for 2.0 h to obtain a uniform first anode catalyst slurry; IrO2, Nafion solution, isopropanol, deionized water, and N-methylpyrrolidone were mixed in a mass ratio of 20%:5%:35%:38%:2% and ultrasonically dispersed for 2.0 h to obtain a uniform second anode catalyst slurry;
[0085] Preparation of cathode catalytic slurry: The cathode catalyst was mixed with ionomer, solvent, deionized water and dispersant in a mass ratio of 20%:5%:40%:33%:2%, and stirred in a planetary ball mill at 2500 rpm for 1.0 h; The cathode catalyst was mixed with ionomer, solvent, deionized water and dispersant in a mass ratio of 15%:5%:40%:38%:2%, and stirred in a planetary ball mill at 2500 rpm for 1.0 h to obtain the second cathode catalytic slurry.
[0086] Preparation of anode modified layer slurry: MoS2 / C composite material, carbon nanotubes and epoxy resin are mixed in a mass ratio of 10%:60%:30% to form anode modified layer slurry;
[0087] An anode-modified layer slurry was coated onto one surface of a perfluorosulfonic acid proton exchange membrane and dried to obtain an anode-modified layer attached to the perfluorosulfonic acid proton exchange membrane; the thickness of the anode-modified layer was 0.8 μm.
[0088] The first anode catalyst slurry was coated onto the surface of the anode modified layer by a transfer method, and then heated on a vacuum adsorption heating plate at 80°C for 2.0 h to form the first anode catalyst layer; the second anode catalyst slurry was coated onto the surface of the first anode catalyst layer by a transfer method, and then heated on a vacuum adsorption heating plate at 80°C for 2.0 h to form the second anode catalyst layer. The total thickness of the anode catalyst layer was 15 μm.
[0089] The first cathode catalyst slurry was coated onto another surface of the membrane using a transfer method and heated on a vacuum adsorption heating plate at 75°C for 2.0 hours to form the first cathode catalyst layer. The second cathode catalyst slurry was coated onto another surface of the perfluorosulfonic acid proton exchange membrane using a transfer method and heated on a vacuum adsorption heating plate at 75°C for 2.0 hours to form the second cathode catalyst layer. The total thickness of the cathode catalyst layer was 10 μm.
[0090] Comparative Example
[0091] Preparation of anode catalyst slurry: IrO2, Nafion solution, isopropanol and deionized water were mixed in a mass ratio of 30%:5%:35%:30% and ultrasonically dispersed for 2.0 h to obtain a uniform anode catalyst slurry;
[0092] Preparation of cathode catalytic slurry: The cathode catalyst, ion polymer, solvent and deionized water were mixed in a mass ratio of 20%:5%:40%:35% and placed in a planetary ball mill and stirred at 2500 rpm for 1.0 h to obtain the second cathode catalytic slurry.
[0093] The anodic catalyst slurry was coated onto the surface of a perfluorosulfonic acid proton exchange membrane by transfer printing and then heated on a vacuum adsorption heating plate at 80°C for 2.0 h to form an anodic catalyst layer with a thickness of 15 μm.
[0094] The cathode catalyst slurry was coated onto another surface of the perfluorosulfonic acid proton exchange membrane by transfer printing, and then heated on a vacuum adsorption heating plate at 75°C for 2.0 h to form a cathode catalyst layer with a total thickness of 10 μm.
[0095] Those skilled in the art will understand that all or part of the processes in the methods of the above embodiments can be implemented by a computer program instructing related hardware. The computer program can be stored in a non-volatile computer-readable storage medium, and when executed, it can include the processes of the embodiments of the above methods. Any references to memory, storage, databases, or other media used in the embodiments provided in this application can include non-volatile and / or volatile memory. Non-volatile memory can include read-only memory (ROM), programmable ROM (PROM), electrically programmable ROM (EPROM), electrically erasable programmable ROM (EEPROM), or flash memory. Volatile memory can include random access memory (RAM) or external cache memory. By way of illustration and not limitation, RAM is available in various forms, such as static RAM (SRAM), dynamic RAM (DRAM), synchronous DRAM (SDRAM), dual data rate SDRAM (DDRSDRAM), enhanced SDRAM (ESDRAM), Synchlink, DRAM (SLDRAM), RAMbus direct RAM (RDRAM), direct memory bus dynamic RAM (DRDRAM), and RAMbus dynamic RAM (RDRAM), etc.
[0096] Those skilled in the art will clearly understand that, for the sake of convenience and brevity, the above-described division of functional units and modules is used as an example. In practical applications, the above functions can be assigned to different functional units and modules as needed, that is, the internal structure of the system described in this application can be divided into different functional units or modules to complete all or part of the functions described above.
Claims
1. A membrane electrode for producing hydrogen by electrolysis of water, characterized in that: The membrane electrode comprises: A proton exchange membrane, an anode catalyst layer and a cathode catalyst layer arranged on both sides of the proton exchange membrane, and an anode modification layer; The content of the anode catalyst in the anode catalyst layer increases from the side close to the proton exchange membrane to the direction away from the proton exchange membrane; The content of the cathode catalyst in the cathode catalyst layer increases from the side close to the proton exchange membrane to the direction away from the proton exchange membrane; The anode modification layer is arranged between the anode catalyst layer and the proton exchange membrane, and the anode modification layer contains a molybdenum-based catalyst for catalyzing the oxidation reaction of hydrogen.
2. The membrane electrode for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The molybdenum-based catalyst in the anode modification layer includes at least one of a MoS2 / C composite material and a MoO2 / C composite material.
3. The membrane electrode for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The membrane electrode further comprises a cathode modification layer; The cathode modification layer is arranged on the outer side of the cathode catalyst layer and is used for adsorbing scale-forming ions in electrolyzed water.
4. The membrane electrode for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The cathode catalyst layer comprises a first cathode catalyst layer located near a proton exchange membrane and a second cathode catalyst layer located far from the proton exchange membrane; the cathode catalyst loading in the first cathode catalyst layer is greater than the cathode catalyst loading in the second cathode catalyst layer.
5. The membrane electrode for producing hydrogen by electrolysis of water according to claim 4, characterized in that: The loading amount of cathode catalyst in the first cathode catalyst layer is 1.5 mg / cm 2 ~2.0mg / cm 2 The loading amount of cathode catalyst in the second cathode catalyst layer is 1.0 mg / cm 2 ~1.5mg / cm 2 .
6. The membrane electrode for producing hydrogen by electrolysis of water according to claim 4, characterized in that: The first cathode catalyst layer and the second cathode catalyst layer are both prepared from cathode catalyst slurry; The cathode catalytic slurry comprises a cathode catalyst, an ion polymer, a solvent, deionized water and a dispersant; and the cathode catalyst is a Pt / CNT composite material.
7. The membrane electrode for producing hydrogen by electrolysis of water according to claim 6, characterized in that: Based on the mass of the Pt / CNT composite material, the content of Pt is 25% to 35%; and the average particle size of Pt is 5nm to 20nm.
8. The membrane electrode for producing hydrogen by electrolysis of water according to any one of claims 4 to 7, characterized in that: The total thickness of the cathode catalyst layer is 5.0 μm to 10.0 μm.
9. The membrane electrode for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The anode catalyst layer comprises a first anode catalyst layer located near a proton exchange membrane and a second anode catalyst layer located far from the proton exchange membrane; the loading amount of the anode catalyst in the first anode catalyst layer is higher than that in the second anode catalyst layer.
10. The membrane electrode for producing hydrogen by electrolysis of water according to claim 9, characterized in that: The loading amount of the anode catalyst in the first anode catalyst layer is 2.5-3.5 mg / cm 2 ; The loading amount of the second anode catalyst is 2.0-2.5 mg / cm 2 .
11. The membrane electrode for producing hydrogen by electrolysis of water according to claim 9, characterized in that: The first anode catalyst layer and the second anode catalyst layer are both prepared from anode catalyst slurry; the anode catalyst slurry includes an anode catalyst, an ion polymer, a solvent, deionized water and a dispersant; the anode catalyst includes one or more of Ir, IrO2, Ru, RuO2, and IrRuOx.
12. The membrane electrode for producing hydrogen by electrolysis of water according to any one of claims 9 to 11, characterized in that: The total thickness of the anode catalyst layer is 10 μm to 20 μm.
13. The membrane electrode for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The proton exchange membrane is selected from one of a perfluorosulfonic acid proton exchange membrane, an organic / inorganic nanocomposite proton exchange membrane, and a fluorine-free proton exchange membrane.
14. A method for preparing a membrane electrode for producing hydrogen by electrolyzing water, the method being used to prepare the membrane electrode according to claims 1 to 13, characterized in that: The preparation method comprises: Preparing an anode catalyst slurry: mixing an anode catalyst with an ion polymer, a solvent, deionized water and a dispersant, and performing ultrasonic dispersion to obtain a uniform first anode catalyst slurry and a second anode catalyst slurry; Preparing cathode catalytic slurry: mixing cathode catalyst with ion polymer, solvent, deionized water and dispersant, placing in a planetary ball mill for stirring and dispersion, to obtain a first cathode catalytic slurry and a second cathode catalytic slurry; Preparing anode modification layer slurry: mixing a molybdenum-based catalyst, a porous carbon material, and a binder to form an anode modification layer slurry; The anode modification layer slurry is coated on one surface of the proton exchange membrane, and the anode modification layer attached to the proton exchange membrane is obtained by drying; The first anode catalyst slurry is coated on the surface of the anode modification layer by a transfer method, and is placed on a vacuum adsorption heating plate for heating to form a first anode catalyst layer; the second anode catalyst slurry is coated on the surface of the first anode catalyst layer by a transfer method, and is placed on a vacuum adsorption heating plate for heating to form a second anode catalyst layer; The first cathode catalyst slurry is coated on the other surface of the proton exchange membrane by a transfer method, and is placed on a vacuum adsorption heating plate for heating to form a first cathode catalyst layer; the second cathode catalyst slurry is coated on the other surface of the proton exchange membrane by a transfer method, and is placed on a vacuum adsorption heating plate for heating to form a second cathode catalyst layer.
15. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 14, characterized in that: A removable cathode modification layer is installed on the surface of the second cathode catalyst layer.
16. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 14, characterized in that: The steps of preparing the anode catalyst slurry include: The mass ratio of the anode catalyst, ion polymer, solvent, deionized water and dispersant is (20% to 30%): (3% to 8%): (30% to 50%): (20% to 45%): (1% to 2%), and then they are mixed and ultrasonically dispersed to obtain a uniform first anode catalyst slurry.
17. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 14, characterized in that: The steps of preparing the anode catalyst slurry include: The anode catalyst, ion polymer, solvent, deionized water and dispersant are mixed in the mass ratio of (15% to 20%): (3% to 8%): (30% to 45%): (25% to 45%): (1% to 2%), and ultrasonic dispersion is performed to obtain a uniform second anode catalyst slurry.
18. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 14, characterized in that: The steps of preparing the cathode catalytic slurry include: The cathode catalyst, ion polymer, solvent, deionized water and dispersant are mixed in a mass ratio of (15% to 20%): (3% to 8%): (30% to 50%): (25% to 45%): (1% to 2%), placed in a planetary ball mill for stirring and dispersion, and a first cathode catalytic slurry is obtained.
19. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 14, characterized in that: The cathode catalyst, ion polymer, solvent, deionized water and dispersant are mixed in a mass ratio of (10% to 15%): (3% to 8%): (30% to 50%): (25% to 45%): (1% to 2%), placed in a planetary ball mill for stirring and dispersion, and a second cathode catalytic slurry is obtained.
20. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water according to claim 14, characterized in that: The thickness of the anode modification layer is 0.5 μm to 1.0 μm.
21. A water electrolysis device, comprising an electrolytic cell, characterized in that: The electrolyzer comprises the membrane electrode for producing hydrogen by electrolyzing water according to any one of claims 1 to 13.
Citation Information
Patent Citations
Water electrolysis membrane electrode, preparation method thereof and hydrogen production device
CN113337844A
Membrane electrode for reducing metal ion pollution of catalyst layer
CN113937328A
Water electrolysis membrane electrode based on proton exchange membrane, preparation method, assembly and application
CN114941153A
PEM water electrolysis hydrogen production membrane electrode and preparation method thereof
CN116254559A
Aqueous organic-hydrogen proton battery
CN116470109A
